Reassessing zircon-monazite thermometry with thermodynamic modelling: insights from the Georgetown igneous complex, NE Australia - Volante, Silvia; Collins, Bill; Blereau, E.; Pourteau, Amaury; Spencer, Christopher; Evans, Noreen; Barrote, Vitor; Nordsvan, A.R.; Li, Zheng-Xiang; Li, J. (SPRINGER, 2020)
Accessory mineral thermometry and thermodynamic modelling are fundamental tools for constraining petrogenetic models of granite magmatism. U–Pb geochronology on zircon and monazite from S-type granites emplaced within a semi-continuous, whole-crust section in the Georgetown Inlier (GTI), NE Australia, indicates synchronous crystallisation at 1550 Ma. Zircon saturation temperature (Tzr) and titanium-in-zircon thermometry (T(Ti–zr)) estimate magma temperatures of ~ 795 ± 41 °C (Tzr) and ~ 845 ± 46 °C (T(Ti-zr)) in the deep crust, ~ 735 ± 30 °C (Tzr) and ~ 785 ± 30 °C (T(Ti-zr)) in the middle crust, and ~ 796 ± 45 °C (Tzr) and ~ 850 ± 40 °C (T(Ti-zr)) in the upper crust. The differing averages reflect ambient temperature conditions (Tzr) within the magma chamber, whereas the higher T(Ti-zr) values represent peak conditions of hotter melt injections. Assuming thermal equilibrium through the crust and adiabatic ascent, shallower magmas contained 4 wt% H2O, whereas deeper melts contained 7 wt% H2O. Using these H2O contents, monazite saturation temperature (Tmz) estimates agree with Tzr values. Thermodynamic modelling indicates that plagioclase, garnet and biotite were restitic phases, and that compositional variation in the GTI suites resulted from entrainment of these minerals in silicic (74–76 wt% SiO2) melts. At inferred emplacement P–T conditions of 5 kbar and 730 °C, additional H2O is required to produce sufficient melt with compositions similar to the GTI granites. Drier and hotter magmas required additional heat to raise adiabatically to upper-crustal levels. S-type granites are low-T mushes of melt and residual phases that stall and equilibrate in the middle crust, suggesting that discussions on the unreliability of zircon-based thermometers should be modulated.